Determination of the U-238 spontaneous fission decay constant without neutron irradiation - Guedes, S.; Hadler, J. C.; Iunes, P. J.; Burke, A. K.; Kazazu, M. H.; Sarkis, JES; Paulo, SR; Tello, C. A. (Kluwer Academic Publ, 2002)
We have developed a methodology for measuring the decay constant of the spontaneous fission of U-238, lambda(f), using nuclear particle track detectors where thermal neutron irradiation is unnecessary. This methodology is based on the fact that the radiation damage caused by spontaneous fission of trans-uranium elements bearing a mass number close to 238 are similar to U-238 spontaneous-fission ones. Loading a thick source of uranium (thickness greater than the fission fragment range) with a small amount of a suitable trans-uranium element (for instance, Pu-242, which presents a spontaneous fission half-life of 6.75(.)10(10) y), it is possible to determine the observation efficiency of a particle-track detector for fission fragments. Procedures concerning our thick source manufacture and uniformity tests of the trans-uranium distribution are also presented. These results make it possible for the exposure of thick uranium sources (without trans-uranium element) to lead to a lambda(f) value.